Leadership Education Based on the Jamaah Concept in Sayyid Qutb’s Tafsir Fî Zhilâl Al-Qur'ân - Toto Santi Aji; Ahmad Yusron (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2022)
The sharp controversy among the scholars regarding the jamaah (congregation) concept has become a more interesting side to finding the answer to the truth. This research focuses on uncovering the congregation concept from interpretations drawn to the contemporary atmosphere and Indonesian climate. The method employed in this research discussion was a research library. The content analysis method was a research method that utilized a set of procedures to draw valid conclusions. This study’s findings included the concept of the understanding congregation, the congregation concept in Tafsir (interpretation) Fî Zhilâl al-Qur'ân, and the congregation concept as one leadership unit. This research conclusion is that the congregation phenomenon, according to Qutb, is not only an obligation for Muslims to uphold it in the world but also something that will impact and determine a person's fate in the hereafter.